A case report and literature review of cognitive malingering and psychopathology - Bosso, Tea; Vischia, Flavio; Keller, Roberto; Vai, Daniela; Imperiale, Daniele; Vercelli, Alessandro (Frontiers in Psychiatry, 2022)
Malingering of cognitive difficulties constitutes a major issue in psychiatric forensic settings. Here, we present a selective literature review related to the topic of cognitive malingering, psychopathology and their possible connections. Furthermore, we report a single case study of a 60-year-old man with a long and ongoing judicial history who exhibits a suspicious multi-domain neurocognitive disorder with significant reduction of autonomy in daily living, alongside a longtime history of depressive symptoms. Building on this, we suggest the importance of evaluating malingering conditions through both psychiatric and neuropsychological assessment tools. More specifically, the use of Performance Validity Tests (PVTs) – commonly but not quite correctly considered as tests of ‘malingering’ - alongside the collection of clinical history and the use of routine psychometric testing, seems to be crucial in order to detect discrepancies between self-reported patient’s symptoms, embedded validity indicators and psychometric results.